2014
DOI: 10.1186/s40337-014-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary examination of a mentor-based program for eating disorders

Abstract: BackgroundThere is a current and pressing need for recovery resources for individuals suffering from eating disorders. Mentoring programs have been useful with other psychiatric disorders such as addictions, and may be useful for individuals recovering from an eating disorder. The present study sought to examine a mentoring program for individuals working towards recovery from an eating disorder.MethodsThe study included mentors (i.e., individuals who have recovered from an eating disorder for an extended peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 31 publications
(63 reference statements)
5
45
0
Order By: Relevance
“…In accordance with the findings of others (Lippi, ; Perez et al., ), this mentoring programme revealed the altruistic motivation of mentors to use their lived experience to help others and affirmed the transformation they have made in their own lives (Fogarty et al., ). Like Perez et al.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In accordance with the findings of others (Lippi, ; Perez et al., ), this mentoring programme revealed the altruistic motivation of mentors to use their lived experience to help others and affirmed the transformation they have made in their own lives (Fogarty et al., ). Like Perez et al.…”
Section: Discussionsupporting
confidence: 84%
“…In accordance with the findings of others (Lippi, 2000;Perez et al, 2014), this mentoring programme revealed the altruistic motivation of mentors to use their lived experience to help others and affirmed the transformation they have made in their own lives . Like Perez et al (2014), our mentors described intrinsic rewards from the mentoring relationship and particularly that it confirmed their own recovery and healthy thought processes (Perez et al, 2014). Notwithstanding the challenges involved with being a mentor, the benefits far outweighed these by validating their own recovery, their redefined thought processes, their repertoire of coping skills and practical advice as a recovered person, further enhancing their own self-worth.…”
Section: E853supporting
confidence: 85%
See 3 more Smart Citations